Pertanggung Jawaban Suatu Negara Terhadap Warganya Yang Melakukan Genosida Diluar Wilayah Yurisdiksi Nasional - Praja Ganda Agung; Dwi Putri Lestarika; Wevy Efticha Sary (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Genocide is a serious crime against human rights and is recognized as a norm of jus cogens in international law, binding all states without exception. The 1948 Genocide Convention obligates participating states to prevent and punish perpetrators of genocide, regardless of the location of the act or the nationality of the perpetrator. However, the implementation of this obligation is often hindered in international legal practice, particularly when citizens of a state commit genocide beyond its territorial jurisdiction. Issues of jurisdiction, sovereignty, and political complexities frequently pose challenges in enforcing justice and accountability for genocide perpetrators. This paper explores the responsibility of states regarding their citizens who commit genocide abroad, analyzing relevant international laws and principles.